DINAMIKA POPULASI KALACEMETI (AMBLYPYGI) DI LUWENG GEBYOK, PURWODADI, TEPUS, GUNUNGKIDUL, DIY - Edi Dwi Atmaja; Budi Dwisetiyani; Isma Dwi Kurniawan (Gunung Djati Conference Series, 2021)
Gunungsewu is one of the largest and well-known karstareas in Indonesia. This karst area has an interesting endokarst(cave) ecosystem. One type of faunas that is common in caveecosystem is whip spiders (Order: Amblypygi). This fauna plays animportant role in maintaining cave ecosystem balance because theyact as top predator. Gebyok is a cave in Gunungsewu that isinhabited by whip spiders. This study aimed to monitor thepopulation dynamic of whip spiders in Gebyok. Data collection wascarried out by direct observation as long as 10 years starting from2010 until 2020. The annual population of whip spiders in Gebyokwas relatively stable (around 30-40 individuals). Meanwhile, thepopulation fluctuated significantly every month. The largestaverage of individuals record occurred in July (5) and the smallestwas in January (0.66). The population dynamic of whip spiders inGebyok was strongly affected by underground river activity.